Predictors of postoperative outcomes for patients with diverticular abscess initially treated with percutaneous drainage - Elagili, Faisal; Luca, Stocchi; Ozuner, Gokhan; Mody, Rekha; Baker, Mark E; Kiran, Ravi P (Elsevier, 2015)
BACKGROUND: The aim of our study was to evaluate factors associated with percutaneous drainage (PCD) failure, complications, and stoma creation for patients undergoing sigmoidectomy for diverticular abscess. METHODS: Data for patients with diverticular abscess greater than or equal to 3 cm in diameter treated with initial PCD from 1994 to 2012 were identified. RESULTS: One hundred fourteen patients (54% male) with a mean age of 57 years and a mean abscess diameter of 7.1 6 2.4 cm were identified. American Society of Anesthesiologists 4 was the only independent factor associated with PCD failure (P , .001). On multivariate analysis, factors associated with postoperative morbidity (n 5 42, 37%) included PCD failure (P 5 .02) and older age (P 5 .04), while risk for stoma creation was associated with PCD failure (P , .001), multiple PCD attempts (P 5 .002), older age (P , .001), Hinchey II (P 5 .03), and increased body mass index (P 5 .01). American Society of Anesthesiologists 4 was the only factor associated with permanent stoma (P 5 .02). CONCLUSIONS: In patients with large diverticular abscess, a successful PCD is associated with reduced postoperative morbidity. However, a large proportion of patients require stoma creation. Significant comorbidity is associated with both failure of PCD and permanent stoma risk.